2003
DOI: 10.1177/0146167202250913
|View full text |Cite
|
Sign up to set email alerts
|

The Ingroup as Pars Pro Toto: Projection From the Ingroup Onto the Inclusive Category as a Precursor to Social Discrimination

Abstract: In an approach to intergroup discrimination and tolerance, it is assumed that the outgroup's difference from the ingroup is evaluated with reference to the prototype of the higher-order category that includes both groups. Two correlational studies yielded evidence that (a) group members tend to perceive their ingroup as relatively prototypical for the inclusive category (projection), (b) members highly identified with both ingroup and inclusive category (dual identity) tend to project most, and (c) relative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
211
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(230 citation statements)
references
References 34 publications
15
211
3
1
Order By: Relevance
“…Waldzus et al (2003) have found that such evaluations moderate the relationship between identification and RIP and they argue that we should only expect such a relationship to appear when evaluations of the superordinate group are positive (which may be related to, but is not the same as superordinate identification). While we did not explicitly measure these evaluations, it is plausible that evaluations of Britain are related to support for independence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Waldzus et al (2003) have found that such evaluations moderate the relationship between identification and RIP and they argue that we should only expect such a relationship to appear when evaluations of the superordinate group are positive (which may be related to, but is not the same as superordinate identification). While we did not explicitly measure these evaluations, it is plausible that evaluations of Britain are related to support for independence.…”
Section: Discussionmentioning
confidence: 99%
“…We should also note here that Waldzus et al (2003) used a different procedure to test for the effect of dual identification, using as predictor a composite score obtained by multiplying the exponential function of both Scottish and British identification (both variables first standardized) -and without entering Scottish and British identification as possible main effects. The reason they advance for such a procedure is that they do not predict any kind of interaction but a specific pattern whereby both ingroup and superordinate identification need to be high in order to produce an effect, whereas a simple product term could also be significant for other patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the underlying rationale for this hypothesis is consistent with the general tenets of infrahumanisation theory, analogies can be found in the ingroup projection model. Mummendey and Wenzel (1999;Wenzel, Mummendey, Weber, & Waldzus, 2003), for example, state that people tend to project, and consequentially perceive the ingroup and its characteristics as more prototypical of the superordinate category than the outgroup and its characteristics. Waldzus, Mummendey, Wenzel, and Boettcher (2004) have shown that when primary school and high school teachers are confronted, both sets of teachers rate the traits of their own group (vs. those of the outgroup) as being more typical of the superordinate category teachers.…”
Section: Targets Of Dehumanisation and Their Moderatorsmentioning
confidence: 99%